Phase-field study of surface irregularities of a cathode particle during intercalation. (1st August 2018) - Santoki, Jay; Schneider, Daniel; Selzer, Michael; Wang, Fei; Kamlah, Marc; Nestler, Britta
Abstract: During the charging and discharging process, lithium manganese oxide spinel, which is a cathodic electrode material of lithium-ion batteries, shows a coexistence of Li-rich and Li-poor phases. The two-phase coexistence is a very important source of capacity fade in lithium-ion batteries. To enhance the understanding of the degradation mechanism, the mathematical modeling of phase separation becomes an important tool. Furthermore, the particle shape polydispersity should be considered to obtain simulated results that are closer to the real kinetics. The present work focuses on the mesoscopic effect of the surface curvature of the cathodic particle, by using the classical Cahn–Hilliard equation. Near the convex region of the particle surface, we find that more sites are available for the applied flux than for the sites that host lithium ions. As a consequence, the onset of phase separation preferentially occurs in high curvature regions of the particle. Furthermore, the elliptical particle with a higher aspect ratio is subjected to the onset of the phase separation, prior to the lower ones. Finally, the effect of variation of parameters on charge dynamics is discussed.